Insurance in extended family networks - Orazio P. Attanasio; Costas Meghir; Corina Mommaerts (Institute for Fiscal Studies (IFS), 2018)
We investigate partial insurance and group risk sharing in extended family networks. Our approach is based on decomposing income shocks into group aggregate and idiosyncratic components, allowing us to measure the extent to which each component is insured. We apply our framework to extended family networks in the United States by exploiting the unique intergenerational structure of the Panel Study of Income Dynamics. We find that over 60% of shocks to household income are potentially insurable within extended family networks. However, we find little evidence that the extended family provides insurance for such idiosyncratic shocks.
Keywords: 330